Informed job entry: Does labour market information speed job-taking in Mozambique? - Ricardo Santos; Sam Jones; Gimelgo Xirinda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
High youth unemployment rates and long school-to-work transition times pose a threat to low-income countries' sustainable growth prospects. Using a randomized control trial experiment conducted in Mozambique, we find strong evidence that providing information on wages and unemployment reduces the time that university graduate job-seekers take to become employed, with different levels of efficacy depending on the type of information provided. This relatively low-cost mechanism can, therefore, reduce labour market frictions at the point of entry, contributing to a quicker intake of qualified human capital into economies where it is relatively scarce.
Keywords: C41; J64; I23; O15; 330; school-to-work; labour; information; randomized control trial